APPLICATIONS ON INTRAVENOUS THERAPY AND CATHETER-ASSOCIATED BLOODSTREAM INFECTION PREVENTION: TECHNOLOGY PROSPECTION* - Silva, Thiago Lopes; Souza, Sabrina de; Rocha, Patrícia Fernandes Albeirice da; Tourinho, Francis Solange Vieira; Manzo, Bruna Figueiredo; Rocha, Patrícia Kuerten (Cogitare Enfermagem, 2023)
Objective: to identify mobile applications on intravenous therapy and prevention of catheter-associated bloodstream infection. Method: technological prospection, with data search in Patent Bases and Virtual Stores, data collection occurred from May to August 2021. Inclusion criteria: mobile applications focused on Intravenous Therapy; mobile applications focused on the prevention of bloodstream infection. The analysis was carried out in a qualitative comparative way, recognizing the functions developed by the applications and their potential for use in clinical practice. Results: 19 applications were selected and organized into themes: applications to assist in catheterization; applications for catheter maintenance; applications on bloodstream infection prevention; and applications on diagnosis of catheter-associated bloodstream infection. Conclusion: The identification of few apps on the theme serves to promote the construction of new apps.